The Design of Tourism Marketing for Maudu Lompoa through Social Engagement in Cikoang Takalar Regency, Indonesia - Sirajuddin Nasir; Hikmah Hikmah; Rilfan Kasi RanteTa’dung; Andi Batary Citta (www.amertainstitute.com, 2023)
This study discusses the cultural and religious marketing of Maudu Lompoa in Cikoang, Takalar Regency. This study aims to identify and analyze the relationship between the Maudu Lompoa celebration and social engagement and marketing concepts used in preserving cultural and religious tourism based on local wisdom in Takalar Regency. In addition, this research is also to find out the promotional designs offered to preserve cultural and religious tourism based on local wisdom inTakalar Regency. This research gives the result that Maudu Lompoa's marketing design emphasizes promotion through social engagement as the main target in the promotion. Where there are local wisdom values that are so strong. One of the efforts to optimize the potential for cultural and religious tourism is by implementing a promotional strategy. Promotion is a one-way flow of information or persuasion made to direct a person or the general public to an action that creates an exchange in marketing. Promotion has an important role in tourism development, because promotion is an attempt to communicate tourism potential to the target market.